Venezuelan equine Encephalomyelitis virus: Structural components - García Tamayo, Jorge; Ryder, Slavia; Ryder, Elena (Investigación Clínica, 2013)
Venezuelan equine encephalomyelitis (VEE) virus, purified in sucrose density gradients was examined with the e1ectron microscope before and after sodium desoxycholate (DOC) treatment. The structure of the nucleocapsid revealed 10 to 12 nm ring shaped units organized into an icosahedral symmetry. Density gradient fractions exhibiting hemagglutinating activity after DOC treatment show 12 to 18 nm particles lined by short projections. These isolated hemagglutinating subunlts are though to correspond to the superficial spikes of VEE virus.